(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Enterobacteria possess acid resistance (AR) systems to survive in acidic environments. Escherichia coli have four proton-consuming AR systems, three of which are inducible: the glutamate-dependent AR2 (Gad), arginine-dependent AR3 (Adi), and lysine-dependent AR4 (Cad). Among these, the Gad system exhibits superior efficiency under highly acidic conditions. This study examined the role of the Gad system in specific growth rate (µ) and extracellular pH (pHex) regulation during fermentation. E. coli MG1655 wild-type (WT) and a ∆gadE mutant strain (lacking the acid-responsive transcriptional activator GadE, essential for gadA and gadBC expression) were cultured in LB medium supplemented with 4 g L-1 glucose at initial pH values of 7.6, 6.5, 5.8, and 5.4. In WT, µ was 0.52 h-1 at pH 7.6, which was decreased by 55% and 70% at pH 5.8 and 5.4, respectively. In the gadE strain, µ was consistently lower, with reductions of 30% at pH 7.6, 25% at pH 6.5 and 5.8, and 30% at pH 5.4, compared to WT. This indicates that the promoting effect of GadE on growth is more prominent at pH 7.6 and 5.4. pHex of growth medium was acidified in WT at all pH conditions due to fermentative acid production. In contrast, the gadE strain showed extracellular alkalization during the logarithmic phase (5–6 h), with pHex increases of 0.79, 0.18, and 0.23 units at pH 7.6, 6.5, and 5.4, respectively. This variation is attributed to the absence of glutamate decarboxylation and proton consumption via the GadC antiporter. Taken together, the Gad system has an important role in bacterial growth, influencing the modulation of pHex.